The effects of dynamic compression on the development of cartilage grafts engineered using bone marrow and infrapatellar fat pad derived stem cells - Luo, Lu; Thorpe, Stephen D; Buckley, Conor T; Kelly, Daniel J (Biomedical materials (Bristol), 2015)
Bioreactors that subject cell seeded scaffolds or hydrogels to biophysical stimulation have been used to improve the functionality of tissue engineered cartilage and to explore how such constructs might respond to the application of joint specific mechanical loading. Whether a particular cell type responds appropriately to physiological levels of biophysical stimulation could be considered a key determinant of its suitability for cartilage tissue engineering applications. The objective of this study was to determine the effects of dynamic compression on chondrogenesis of stem cells isolated from different tissue sources. Porcine bone marrow (BM) and infrapatellar fat pad (FP) derived stem cells were encapsulated in agarose hydrogels and cultured in a chondrogenic medium in free swelling (FS) conditions for 21 d, after which samples were subjected to dynamic compression (DC) of 10% strain (1 Hz, 1 h d−1) for a further 21 d. Both BM derived stem cells (BMSCs) and FP derived stem cells (FPSCs) were capable of generating cartilaginous tissues with near native levels of sulfated glycosaminoglycan (sGAG) content, although the spatial development of the engineered grafts strongly depended on the stem cell source. The mechanical properties of cartilage grafts generated from both stem cell sources also approached that observed in skeletally immature animals. Depending on the stem cell source and the donor, the application of DC either enhanced or had no significant effect on the functional development of cartilaginous grafts engineered using either BMSCs or FPSCs. BMSC seeded constructs subjected to DC stained less intensely for collagen type I. Furthermore, histological and micro-computed tomography analysis showed mineral deposition within BMSC seeded constructs was suppressed by the application of DC. Therefore, while the application of DC in vitro may only lead to modest improvements in the mechanical functionality of cartilaginous grafts, it may play an important role in the development of phenotypically stable constructs.